The effects of temperature and shading on mortality and development rates of Aedes aegypti (Diptera: Culicidae). Issue 2 (15th November 2019) - Sukiato, Febrianne; Wasserman, Ryan J.; Foo, Su Chern; Wilson, Robyn F.; Cuthbert, Ross N.
ABSTRACT: Urbanization has caused an increase in favorable habitats for Aedes aegypti (Diptera: Culicidae), given their ability to reproduce in small and often non‐degradable artificial water‐containers. While much work has been done on Ae. aegypti biology and ecology in urban landscapes, the role of shading on immature stages as an independent factor from temperature, and any possible interactions between these factors, remains unexamined. We assessed how temperature and shading affected egg hatch‐rate, larval/pupal mortality, and larval development to adult stage under different factorial temperature (28; 31; 34; 37; 40° C) and shade (0%, 3, 100 lux; 40%, 1, 860 lux; 75%, 775 lux; 100%, 0 lux) regimes. Hatch‐rate was significantly lower at 37° C (57 %), and no eggs hatched at 40° C. There was no significant effect caused by shading on hatchability. Larval and pupal mortality at 37° C was significantly higher (35%) compared to lower temperature groups, while the effects of shading were emergent at low temperatures. Developmental times from hatching to adult emergence were significantly reduced with increasing temperatures and with greater light exposures. The eco‐physiological response of Ae. aegypti larvae to temperature and light regimes suggest a photosensitivity previously unstudied in this species.